Pre- and Post-Harvest Regulation of Fruit Quality in Sweet Orange - Rehman, Muneer (Curtin University, 2018)
Poor colour of orange fruit causes serious economic losses to growers. Spray application of abscisic acid, prohexadione-Ca, paclobutrazol or methyl jasmonate at 6 or 3 weeks before harvest promoted fruit colour in M7 Navel. Hot water (50 °C) 5 min dip alone or combined with thiabendazol, methyl jasmonate 1 min dip (0.1 - 0.50 mM) or nitric oxide (5 - 20 µL L-1) fumigation reduced chilling injury in Midknight Valencia and Lane Late oranges.